2006
DOI: 10.1183/09031936.06.00138105
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the clinical presentation and management of airflow obstruction

Abstract: The aim of the present study was to explore differences in the clinical expression, clinical diagnoses and management of airway diseases in a primary-care setting.Patients aged o35 yrs who had ever smoked were enrolled when they presented for any reason to one of eight rural primary-care practices. Respiratory symptom questionnaires and spirometry were administered. In total, 1,034 patients had acceptable and reproducible spirometry, of whom 550 (53%) were males and 484 (47%) were females.Males smoked more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 15 publications
1
42
1
1
Order By: Relevance
“…In addition, we found that sex and MRC dyspnoea grade at study entry, and smoking status are risk factors. Females report more breathlessness for similar levels of airflow obstruction and are more likely to receive treatment for COPD than males [35,36]. They may, therefore, be more likely to be classified as having an exacerbation.…”
Section: Mortalitymentioning
confidence: 99%
“…In addition, we found that sex and MRC dyspnoea grade at study entry, and smoking status are risk factors. Females report more breathlessness for similar levels of airflow obstruction and are more likely to receive treatment for COPD than males [35,36]. They may, therefore, be more likely to be classified as having an exacerbation.…”
Section: Mortalitymentioning
confidence: 99%
“…Female COPD patients report a higher level of dyspnoea for the same level of ventilatory impairment than men. 56,57 In the Confronting COPD International Survey, women were more likely to report severe dyspnoea than men (odds ratio (OR) 1.30, 1.10-1.54), with similar cough (OR 1.08, 0.92-1.27) and less sputum (OR 0.84, 0.72-0.98), despite significantly lower pack-years of smoking (mean (SD) 36 (29) vs. 46 (35) pack-years). 58 Women enrolled in the National Emphysema Treatment Trial (NETT) also experienced greater dyspnoea and lower quality of life than men matched for precent predicted FEV 1 , age, proportion of the lung affected by emphysema, and pack-years.…”
Section: Symptomsmentioning
confidence: 99%
“…Despite this, they were more likely to receive smoking cessation advice than males, indicating these diagnostic and reporting biases can adversely affect management for both sexes. The findings by DALES et al [7] also suggest that females may sometimes be prescribed respiratory medication inappropriately, without a relationship to airway obstruction or a clear diagnostic ''label'', increasing the possibility of side-effects without definite efficacy. Conversely, males may receive medication less often for milder airway obstruction, with potential detrimental effect, although the consequences of this are less clear for COPD than asthma.…”
mentioning
confidence: 99%
“…By contrast, DALES et al [7] reported the clinical presentation and historical features in ever-smokers in a primary care setting in Canada. Respiratory symptom questionnaires and spirometry were administered in 1,034 (53% males) patients attending their general practitioner for any reason, but who had smoked at least 20 packs of cigarettes in their life.…”
mentioning
confidence: 99%
See 1 more Smart Citation